Studi Kasus Kemampuan Berpikir Kritis Isu Lingkungan Lokal Mahasiswa Pendidikan IPA Semester 6 Jurusan Biologi UNIMED - Indriani Laurensia Br Tarigan; Lisnawaty Simatupang (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study aims to profile the conceptual understanding levels and detect misconceptions regarding the eutrophication of Lake Toba among pre-service biology teachers. A Two-Tier Diagnostic Test was developed to measure four critical thinking indicators: interpretation, analysis, inference, and evaluation. Student responses were classified into four cognitive states: Concept Understanding (PK), Misconception (MK), Partial Concept (KP), and No Understanding (TP). The results revealed a linear degradation of scientific reasoning as the complexity of critical thinking indicators increased. The percentage of students with full Concept Understanding (PK) dropped drastically from interpretation (35%), analysis (19%), and inference (11%), leaving only 4% at the evaluation indicator. Conversely, the "No Understanding" (TP) state dominated higher-order thinking dimensions, reaching 44% in evaluation. A comparative analysis of tier averages confirmed a consistent false-positive phenomenon (except in evaluation), where the average score for the selection answer (Tier 1) was routinely higher than the explanatory reason (Tier 2), with the widest gap observed in the inference indicator (T1: 48%, T2: 25%). These findings confirm a profound scientific reasoning crisis among pre-service teachers, where students successfully guess or select correct surface-level answers but fail to construct valid causal arguments.